How Employer Branding Attract the Generation Z Students to Join on Start-up Unicorn - Dediek Tri Kurniawan; Andro Agil Nur Rakhmad; Ooji Futari II; Yesiana Ihda Kusnayain (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
The development of the world revolution has changed the paradigm and stigmas of organizational quality to increase competitiveness from various human resource perspectives. Increasing global challenges have made the employer branding strategy a concern for global research. This study examines the effect of employer branding on Generation Z students' attractiveness and employer choices at unicorn start-ups in Indonesia. This study uses the Structural Equation Model Partial Least Square (SEM-PLS). This study got a total of 200 respondents who fit the criteria. This study's dimensions of employer branding are work culture, ethics & CSR, diversity, and salary & incentives. From the results of this study, the dimensions that proved to be influential were Ethics and CSR, and Diversity. Besides, work culture and salary & incentives are not proven to significantly affect the attractiveness of Generation Z students to Indonesian unicorn start-ups. Social media is proven to have a significant effect on both attractiveness and choice of workplace (employer of choice) Generation Z students at Indonesian unicorn start-ups.